Hook Breathing Facilitates SaO2 Recovery After Deep Dives in Freedivers With Slow Recovery - Fernández, Fran de Asís; Rodríguez-Zamora, Lara; Schagatay, Erika (Frontiers in Physiology, 2019)
To facilitate recovery from hypoxia many freedivers use a breathing method called "hook breathing" (HB) after diving, involving an interrupted exhale to build up intrapulmonary pressure. Some divers experience a delay in recovery of arterial oxygen saturation (SaO2) after diving, interpreted as symptoms of mild pulmonary edema, and facilitated recovery may be especially important in this group to avoid hypoxic “blackout”. We examined the influence of HB on recovery of SaO2 in freedivers with slow recovery (SR) and fast recovery (FR) of SaO2 after 30 m free immersion apnea (FIM) dives. Twenty-two male freedivers, with a mean(SD) personal best in FIM of 57(26)m, performed two 30 m dives, one followed by HB and one using normal breathing (NB) during recovery, at different days and weighted order. SaO2 and heart rate (HR) were measured via pulse oximetry during recovery. The SR group (n=5) had a faster SaO2 recovery using HB while the FR group (n=17) showed no difference between techniques. At 105s the SR group reached a mean(SD) SaO2 of 95(5)% using HB, while using NB their SaO2 was 87(5)% (P<0.05), and 105–120 s after surfacing SaO2 was higher with HB (P<0.05). In SR subjects, the average time needed to reach 95% SaO2 with HB was 60s, while it was 120s at NB (P<0.05). HR was similar in the SR group, while it was elevated at HB in the FR group (P<0.05). We conclude that HB is efficiently increases SaO2 recovery in SR individuals, but not in FR group. The proposed mechanism is that increased pulmonary pressure with HB will reverse any pulmonary edema and facilitate oxygen uptake in divers with delayed recovery.